A Rare Alder‐ene Cycloisomerization of 1, 6‐Allenynes. Issue 12 (1st February 2022) - Joyce, Liam M.; Drew, Melanie A.; Tague, Andrew J.; Thaima, Thanaphat; Gouranourimi, Ali; Ariafard, Alireza; Pyne, Stephen G.; Hyland, Christopher J. T.
Abstract: Thermally induced cycloisomerization reactions of 1, 6‐allenynes gives α‐methylene‐γ‐lactams via intramolecular Alder‐ene reactions. The mechanism is supported by computational and deuterium labelling studies. This thermal, non‐radical method enables the discovery of a hitherto unknown route that proceeds via a divergent mechanism distinct from the previous [2+2] cycloisomerization manifold. Abstract : Novel Alder‐ene reaction : Thermally induced intramolecular Alder‐ene reactions of 1, 6‐allenynes gives α‐methylene‐γ‐lactams via a mechanism distinct from previous [2+2] cycloisomerization manifolds of related skeletons. The mechanism involves an unusual transfer of the allene‐hydrogen and is supported by computational and deuterium labelling studies. The reaction is favoured by the electron‐deficient nature of the propiolamide moiety and the absence of substituents on the termini of both the allene "ene" moiety and the alkyne of the 1, 6‐allenyne.